PENGEMBANGAN MEDIA CARS BERBASIS AUGMENTED REALITY MATERI SISTEM TATA SURYA MTS/SMP - Sarura, Vionita Alya; Istiqomah, Laili Nur; Ratno, Puspoko Ponco; Wulandari, Ratna Wahyu (Universitas Tanjungpura, 2025)
Education has an important role in human life because it allows individuals to develop potential in aspects of knowledge, attitudes and skills. An effective learning process can support optimal student growth and development. This research aims to: Analyzing the feasibility of CARS media (Card Antarariksa republiksa solar) based on augmented reality in class VII MTsN 1 Kota Kediri, Assessing its validity and practicality in improving student learning outcomes. The research uses the ADDIE development model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 34 students of class VII-K MTsN 1 Kota Kediri. Data were obtained through interviews and questionnaires validated by two lecturers of Tadris Sains IAIN Kediri, two teachers of MTsN 1, and four students. The validity of the media was analyzed using a Likert scale, while its effectiveness was measured through the N-Gain test and Wilcoxon hypothesis test based on the pre-test and post-test results. The validation results show that CARS media is categorized as very valid in terms of media, material, and assessment.